2014
DOI: 10.1007/s10620-014-3416-8
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Evaluating HCV in an Uninsured Population

Abstract: Noninvasive assessment can accurately exclude advanced fibrosis. Despite access to care, the utility of evaluating to initiate HCV treatment is low suggesting that eliminating the barrier to health care may not increase HCV treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Of 2084 patients, 38% had cirrhosis and 56% had received prior treatment for HCV. SVR rates were 31% (95% CI: [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]) and 50% (95% CI: 44-56) in boceprevir patients with and without cirrhosis, respectively. SVR rates were 46% (95% CI: 42-50) and 60% (95% CI: 57-64) in telaprevir patients with and without cirrhosis, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 2084 patients, 38% had cirrhosis and 56% had received prior treatment for HCV. SVR rates were 31% (95% CI: [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]) and 50% (95% CI: 44-56) in boceprevir patients with and without cirrhosis, respectively. SVR rates were 46% (95% CI: 42-50) and 60% (95% CI: 57-64) in telaprevir patients with and without cirrhosis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Access to care and HCV medications is an important component of care. A recent study in the DAA era of uninsured patients showed that despite access to care and medications, the utility of evaluation and initiation of treatment remained low suggesting that eliminating barriers to health care may not lead to an increase in treatment rates …”
Section: Discussionmentioning
confidence: 99%
“…In a similar uninsured population, a low FIB-4 <1.45 effectively excluded advanced fibrosis. 27 In the Chronic Hepatitis Cohort Study, the mean FIB-4 level among persons with F3 (severe fibrosis) on International Association for the Study of the Liver classification based on biopsy was 2.32 and that for F4 (cirrhosis) was 4.12. 16 Because the sensitivity for liver cirrhosis has been reported to be only 38% for ultrasound alone but 77% for CT scan alone, 28 we required at least CT evidence of cirrhosis for patients with an intermediate elevation of FIB-4 (>1.45-3.25).…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective cohort, data on noninvasive staging for 148 patients with chronic HCV infection showed that over one‐third had advanced fibrosis based on FIB‐4 levels and imaging studies supporting cirrhosis. In a similar uninsured population, a low FIB‐4 <1.45 effectively excluded advanced fibrosis . In the Chronic Hepatitis Cohort Study, the mean FIB‐4 level among persons with F3 (severe fibrosis) on International Association for the Study of the Liver classification based on biopsy was 2.32 and that for F4 (cirrhosis) was 4.12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation